2018
DOI: 10.1002/chem.201801008
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Europium Complexes for Visualizing Fluctuations in Mitochondrial ATP Levels in Living Cells

Abstract: The ability to study cellular metabolism and enzymatic processes involving adenosine triphosphate (ATP) is impeded by the lack of imaging probes capable of signalling the concentration and distribution of intracellular ATP rapidly, with high sensitivity. We report here the first example of a luminescent lanthanide complex capable of visualizing changes in the concentration of ATP in the mitochondria of living cells. Four cationic europium(III) complexes [Eu.1–4]+ have been synthesized and their binding capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 79 publications
0
49
0
Order By: Relevance
“…An exception to this is [Eu.2] + , where the ATP titration in the presence of 5 mM MgCl 2 produced a two-step binding prole, which prevented the determination of a binding constant, due to the occurrence of multiple equilibria involved in the binding of [Eu.2] + to both ATP and ATP-Mg, as indicated by previously reported mass spectral data. 38 Binding 40 This revealed that q ¼ 1 for each complex in the absence of added anions, but q ¼ 0 in the presence of ATP or ADP, consistent with displacement of the coordinated water molecule from each complex upon binding ATP or ADP. In the presence of 5 mM AMP, a q value of 0.3-0.7 was found, indicating partial hydration, possibly reecting the weaker monodentate binding of AMP, in accordance with previous examples of phosphate binding at lanthanide centres.…”
Section: Eu(iii) Emission Spectral Changes Upon Phosphoanion Bindingmentioning
confidence: 79%
“…An exception to this is [Eu.2] + , where the ATP titration in the presence of 5 mM MgCl 2 produced a two-step binding prole, which prevented the determination of a binding constant, due to the occurrence of multiple equilibria involved in the binding of [Eu.2] + to both ATP and ATP-Mg, as indicated by previously reported mass spectral data. 38 Binding 40 This revealed that q ¼ 1 for each complex in the absence of added anions, but q ¼ 0 in the presence of ATP or ADP, consistent with displacement of the coordinated water molecule from each complex upon binding ATP or ADP. In the presence of 5 mM AMP, a q value of 0.3-0.7 was found, indicating partial hydration, possibly reecting the weaker monodentate binding of AMP, in accordance with previous examples of phosphate binding at lanthanide centres.…”
Section: Eu(iii) Emission Spectral Changes Upon Phosphoanion Bindingmentioning
confidence: 79%
“…Indeed, a derivative of [Eu.L 1 ] + has already been shown to permeate living cells and localise to specific subcellular compartments. 58 Direct Monitoring of Bicarbonate Transport by Emission Spectroscopy…”
Section: Discussionmentioning
confidence: 99%
“…2019, 25,2684 -2694 www.chemeurj.org ATP, adeninel ocates outsidet he pyrene dimer.P yrene-based Zn II complex 52,p resented by Xing and co-workers, has similar binding and fluorescence properties compared to those found for 51.B ased on the monomer/excimeri ntensity ratio, the selectivity order in a1 0mm HEPES buffer (pH 7.4) of ATP > ADP % GTP > TTP % CTP > AMP > UTP % PPi was observed. [36] Excimer emission is also ak ey feature of the Butler's tripodalr eceptor (60), which can detect ATPa nd quantify apyrase activity. [37] Our group used the anthracene-based DPA-Zn II complex 53 for experimental quantificationo fp-p stackingi nteractions between anthracenea nd nucleobases.…”
Section: Metal-based Receptorsmentioning
confidence: 99%
“…An improved selectivity for ATPw as achieved with complex 69. [60] This probe can detect changes in concentration of mitochondrial ATP( 1-5 mm)a nd is minimally perturbed by changes in pH, dissolved oxygen, or the presence of proteins. Ta ng and co-workersr eported another turn-onc yclam-based probe (70), which was found to be selective for ATPo ver ADP andA MP.…”
Section: Metal-based Receptorsmentioning
confidence: 99%